Pengaruh Kualitas Layanan, Kualitas Produk dan Harga Terhadap Kepuasan Pelanggan Salon di Tanjung Tabalong Kalimantan Selatan - Ike Rachmawati; Bambang Widjanarko Susilo; Sulartopo Sulartopo; Febrytahanuji; Haryo Kusumo (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to explore how service quality, product quality, and pricing strategies affect the level of customer satisfaction at the RCP Salon located in Tanjung, Tabalong, South Kalimantan. The approach used in this study is quantitative with empirical methods combined with descriptive and inferential statistical analysis. The subjects in this study are customers who have used RCP salon services, with a sample of 100 people who were selected purposively. The data collection technique was carried out through the distribution of questionnaires using the Likert scale, while the data analysis was carried out by multiple linear regression using the help of SPSS software version 22. The results of the study show that service quality, product quality, and price have a significant influence on customer satisfaction. These findings confirm that are key components in creating a satisfying customer experience. These findings provide important insights for salon business managers to always improve service quality, maintain product quality, and set prices that are in line with the value felt by customers. Overall, this research provides a strategic direction for the development of services oriented towards customer satisfaction and loyalty, while strengthening the competitiveness of the salon business in the midst of competition in the beauty services industry.